∫ c o s 3 x d x = ψ γ ( c o s 2 x s i n x + l n ( c o s x α + s i n x ) )
Where γ + ψ are co-prime find
γ + ψ + α − 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sorry for the incorrect answer @Trevor B. .. Thats embarrassing careless me, how did you know the incorrect answer was 3 any ways This problem can also be solved with out integration by parts let u = c o s x , and s = s i n x = ∫ u 3 1 = ∫ u 4 u = ∫ ( 1 − s 2 ) 2 u = ∫ 4 1 u ( 1 + s 1 + 1 − s 1 ) 2 = 4 1 ∫ ( ( 1 + s ) 2 u + ( 1 − s ) 2 u ) + 2 1 ∫ ( 1 − s ) 2 u = 4 1 ( 1 + s − 1 + 1 − s 1 ) + 4 1 ∫ ( 1 + s u + 1 − s u ) = 2 u 2 s + 4 1 l n ( 1 − s 1 + s ) = 2 1 ( u 2 s + l n ( u 1 + s ) ) = 2 1 ( c o s 2 x s i n x + l n ( c o s x 1 + s i n x ) )
You also need a + C in the problem statement.
Log in to reply
haha, you remind me of my math teacher
Log in to reply
Well, you do need it. If you search "The Importance of + C " you will find a note I wrote explaining why forgetting it can be a very bad mistake.
Log in to reply
@Trevor B. – i know , especially in physics, i tend to ignore them when there aren't necessary, not that i am correct though.
I sent the clarification (1+2+1=4) :P
Log in to reply
sorry about that, i should me more careful about it.
Problem Loading...
Note Loading...
Set Loading...
The integral is the famous integral of secant cubed .
The integral can be done by parts, using this formula. ∫ u d v = u v − ∫ v d u
Let u = sec x , d u = sec x tan x d x , v = tan x , and d v = sec 2 x d x . Plugging in to the formula, ∫ sec 3 x d x = sec x tan x − ∫ sec x tan 2 x d x = sec x tan x − ∫ sec x ( sec 2 x − 1 ) d x = sec x tan x − ∫ sec 3 x d x + ∫ sec x d x Move the integral of sec 3 x back over to the LHS. 2 ∫ sec 3 x d x = sec x tan x + ∫ sec x d x = sec x tan x + ln ∣ sec x + tan x ∣ + C Divide each side by 2 to get the final answer. ∫ sec 3 x d x = 2 1 ( sec x tan x + ln ∣ sec x + tan x ∣ ) + C
Rearranging of the trigonometric functions shows this. 2 1 ( sec x tan x + ln ∣ sec x + tan x ∣ ) + C = 2 1 ( cos 2 x sin x + ln ( cos x 1 + sin x ) ) + C Thus, γ = 1 , ψ = 2 , and α = 1 , so γ + ψ + α − 1 = 3